Diversity of fungal endophytes at different maturity levels of Cryptolepis buchanani leaves - Bhardwaj, Sujata; Abbas, N. S.; Kaula, Babeeta C; Prakash, Anil (Current Botany, 2023)
A study on endophytic microflora diversity at each level and portion of the leaves of Cryptolepis buchanani, a medicinal plant used by tribals of Madhya Pradesh, India was carried out in the present investigation. As many as 383 isolates from 360 discs of leaves belonging to 17 fungal species and 9 isolates, which did not show any sporulation (sterile), were recovered. Among the 17 identified species, hyphomycetes is the dominant class and Aspergillus, Colletotrichum and Khuskia are the dominant genera. Colonization frequency (CF) was higher in mature leaves (78.3%) and comparatively lower in younger leaves (51.1%) and there was a marginal decrease in CF from the base of the leaf (66.7%) towards the leaf apex (62%). Statistical analysis revealed that level of the leaf had a significant effect on CF and diversity of fungal endophytes, while as leaf sub-parts had little influence. Biochemical characterization of the endophyte revealed the production of various enzymes viz. protease, amylase, lipase, cellulase, xylanase and pectinase. These fungal enzymes can be tapped for food, pharma, beverages, textiles, confectionaries, and leather industries. These bioactive natural products are easy to process as they are usually more stable than products obtained from other sources. The enzymatic activities also help to get a better insight into the host-endophyte relationship. However, the world of fungal endophytes needs to be researched extensively for production of plant based novel eco-friendly biomolecules in cost-effective manner.